Comparative Analysis of Population Aging and Socio-economic Implications in Thailand and Japan - Choomplang, Nattadech; Negishi, Yasushi (Thammasat Review, 2025)
Thailand and Japan are notable examples of rapidly aging societies in Asia, each experiencing its demographic shift under different population structures and socio-economic scenarios. The aging process in these two countries highlights various socio-economic strengths and challenges. This paper examines the extent of the aging process and its socio-economic implications in Thailand and Japan from a comparative perspective, considering their distinct demographic and socio-economic conditions. The data for this analysis are sourced from secondary sources in both countries. Various indices of aging and descriptive statistics are employed for data analysis. The growth of the aging population in both countries is rapid, although the pace and timing of this growth differ due to the dynamic and variable nature of the transition. In both Thailand and Japan, the elderly face several challenges in managing their economic resources and often rely on familial, social, or state support. Socio-economic policies are crucial for addressing these challenges. Policy considerations must focus on improving the quality of life for the elderly, aiming to make them a more productive and healthier group. This requires the assistance and cooperation of private entities, non-governmental organizations, and society at large.